- Analysis of the Effects of Group Progressive Resistance Training on Interleukin-8 (IL-8), Interleukin-18 (IL-18), Interleukin-6 (IL-6), Interleukin-12 (IL-12) and VO2max, VEmax, O2pulsemax, HRmax, and mMRC in Elderly Patients with Chronic Obstructive Pulm: Resistance Training on Interleukin-8 (IL-8), Interleukin-18 (IL-18), Interleukin-6 (IL-6), Interleukin-12 (IL-12) - Sun, Yijia (Journal of Medical Biochemistry, 2024)
Objective To investigate the effects of implementing group progressive resistance training on Maximal Oxygen consumption (VO2max), Maximum Ventilation per minute (VEmax), Maximeal Oxygen pulse (O2pulsemax), Maximum Heart Rate (HRmax), and Modified Medical Research Councildyspneascale (mMRC) in elderly patients with chronic obstructive pulmonary disease. Method: 114 elderly patients with chronic obstructive pulmonary disease treated in the hospital from May 2022 to May 2024 were collected and divided into two groups based on different training methods. The conventional group (n=57) received routine rehabilitation training, while the organization group (n=57) received group progressive resistance training. To compare the improvement of training compliance, Cardiopulmonary Exercise Testing (CPET) parameters, serum inflammatory factors, lung function indicators, and mMRC score between two groups before training, 2 weeks of training, and 4 weeks of training. Results: Before training, there was no statistically significant difference (P>0.05) between the two groups in terms of Training Compliance Score (TCS), CPET parameter indicators, serum inflammatory factors, and mMRC score. After 2 weeks and 4 weeks of training, both groups of patients showed an increase in reported scores on training frequency, training intensity, autonomous training, and self training. The levels of VO2max, VEmax, O2pulsemax, and HRmax in both groups increased. In the comparison of these two groups of indicators, organization was higher than conventional group, and the difference was statistically significant (P<0.05). The levels of Interleukin-8 (IL-8), Interleukin-18 (IL-18), Interleukin-6 (IL-6), and Interleukin-12 (IL-12) decreased in both groups, and the mMRC scores of both groups decreased. The comparison between the two results showed that the organization was lower than conventional, and the difference was statistically significant (P<0.05). Conclusion: Group progressive resistance training can help improve the compliance of elderly patients with chronic obstructive pulmonary disease with training, reduce the body’s inflammatory response, improve VO2max, VEmax, O2pulsemax, HRmax levels, and alleviate breathing difficulties.